The “Hip Fracture” Bundle—Experiences, Challenges, and Opportunities - Azeem Tariq Malik MBBS; Safdar N. Khan MD; Thuan V. Ly MD; Laura Phieffer MD; Carmen E. Quatman MD, PhD (Geriatric Orthopaedic Surgery & Rehabilitation, 2020)
Introduction: With growing popularity and success of alternative-payment models (APMs) in elective total joint arthroplasties, there has been recent discussion on the probability of implementing APMs for geriatric hip fractures as well. Significance: Despite the growing interest, little is known about the drawbacks and challenges that will be faced in a stipulated “hip fracture” bundle. Results: Given the varying intricacies and complexities of hip fractures, a “one-size-fits-all” bundled payment may not be an amenable way of ensuring equitable reimbursement for participating physicians and hospitals. Conclusions: Health-policy makers need to advocate for better risk-adjustment methods to prevent the creation of financial disincentives for hospitals taking care of complex, sicker patients. Hospitals participating in bundled care also need to voice concerns regarding the grouping of hip fractures undergoing total hip arthroplasty to ensure that trauma centers are not unfairly penalized due to higher readmission rates associated with hip fractures skewing quality metrics. Physicians also need to consider the launch of better risk-stratification protocols and promote geriatric comanagement of these patients to prevent occurrences of costly adverse events.